Effects of control techniques and damper constraint on the performance of a semi-active magnetorheological damper - K. , Hudha; Jamaluddin, H.; Samin, P. M.; Rahman, R. A. (Inderscience Publishers, 2005)
Semi-active dampers change their damping force in real time by simply changing the damping coefficient according to a control policy. In this study, a number of semi-active control algorithms namely modified skyhook, modified groundhook and modified hybrid skyhook-groundhook controllers are evaluated to be used with a magnetorheological damper. The effectiveness of these control algorithms in disturbance rejection are investigated along with their ability to consistently provide the target force in the same direction with the damper velocity to overcome the damper constraint. From the simulation and experimental results, the modified hybrid skyhook-groundhook controller shows significant improvement in body acceleration, body displacement, suspension displacement without allowing excessive wheel acceleration magnitude. The modified hybrid skyhook-groundhook controller is also superior to the counterparts in overcoming the damper constraint by producing the target forces consistently in the same sign with the damper velocity. Copyright Â© 2005 Inderscience Enterprises Ltd.